Climate obligations and social norms. (May 2023) - Collins, Stephanie
Many governments are failing to act sufficiently strongly on climate change. Given this, what should motivated affluent individuals in high-consumption societies do? This paper argues that social norms are a particularly valuable target for individual climate action. Within norm-promotion, the paper makes the case for a focus on anti-fossil fuel norms specifically. Section 1 outlines gaps in the existing literature on individuals' climate change obligations. Section 2 characterises social norms. Section 3 provides seven reasons why social norms are a particularly worthy target for individual climate actors. Section 4 asks which social norms individuals should emphasise, arguing that anti-fossil fuel norms have advantages over emissions reduction and offsetting norms. Section 5 outlines the pathways and mechanisms individuals might exploit to promote anti-fossil fuel norms.